2017
DOI: 10.1002/bjs5.22
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of frailty as a predictor of morbidity and mortality after major abdominal surgery

Abstract: BackgroundFrailty is associated with poor prognosis, but the multitude of definitions and scales of assessment makes the impact on outcomes difficult to assess. The aim of this study was to quantify the effect of frailty on postoperative morbidity and mortality, and long‐term mortality after major abdominal surgery, and to evaluate the performance of different frailty metrics.MethodsAn extended literature search was performed to retrieve all original articles investigating whether frailty could affect outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 64 publications
(73 reference statements)
2
66
0
2
Order By: Relevance
“…We observed that the incidence of post‐operative morbidity raised from 31% to 49.5% and 90‐day mortality from 1.4% to 7.5% in the youngest group compared to the oldest group respectively. Whilst not statistically significant, these figures require consideration and may be indicators of the failure‐to‐rescue syndrome defined as the probability of death after a surgical complication . In fact, at the multivariate analysis, we observed that age over 75 years was the only independent factor for having complications after liver resection with 2.5‐fold increased risk.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We observed that the incidence of post‐operative morbidity raised from 31% to 49.5% and 90‐day mortality from 1.4% to 7.5% in the youngest group compared to the oldest group respectively. Whilst not statistically significant, these figures require consideration and may be indicators of the failure‐to‐rescue syndrome defined as the probability of death after a surgical complication . In fact, at the multivariate analysis, we observed that age over 75 years was the only independent factor for having complications after liver resection with 2.5‐fold increased risk.…”
Section: Discussionmentioning
confidence: 77%
“…In fact, at the multivariate analysis, we observed that age over 75 years was the only independent factor for having complications after liver resection with 2.5‐fold increased risk. This risk is likely to be the expression of the age‐related frailty, a state of vulnerability to poor resolution of homeostasis following a stressor event. It develops as a consequence of cumulative decline across multiple physiological systems, and it has been usually associated with cells ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed remarkably high 30‐day, 180‐day, and 1‐year mortality in Medicare patients with frailty who underwent an EGS. Similar to findings from other studies, patients with frailty had at least 2 times the risk of 1‐year mortality compared with non‐frail patients . Additionally, this relationship was dose dependent, where a higher degree of frailty conferred a greater risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…5,[10][11][12][13] In contrast, the frailty index is a multidimensional score, which may qualify for being considered as a complementary predictor of adverse outcomes, since it relies on a different definition than previous parameters. [14][15][16][17] However, to date no studies tested its association with short-term postoperative outcomes after RNU. Based on this unmet need, we investigated rates and trends over time of frail patients undergoing RNU, using the Johns Hopkins Adjusted Clinical Groups (ACG) frailty-defining diagnoses indicator.…”
mentioning
confidence: 99%